Impact of MBA Education on Students’ Values: Two Longitudinal Studies - Krishnan, Venkat R. (Journal of business ethics, 2008)
The impact of 2-year residential fulltime MBA program on students’ values was studied using a longitudinal design and data collected over 7 years from a business school in India. Values were measured when students entered the program, and again when they graduated. Sample in Study 1 consisted of 229 students from three consecutive graduating classes. Rank-order or ipsative measure of values was used. Results of matched sample t-tests show that self-oriented values like a comfortable life and pleasure become more important and others-oriented values like being helpful and polite become less important over 2 years. The moderating role of sex and functional specialization are also analyzed. Study 2 used a non-ipsative measure of values and a sample of 138 students from two consecutive graduating classes. Results show that management education enhances self-monitoring and importance of self-oriented values and reduces the importance of others-oriented values. The effect on both sets of values remains significant even after controlling for self-monitoring.